The Anatomy of the Gaanv: The Relationship of Space and Place with Caste, Religion, and Gender - Metcalfe, Priya; Schapper, Jake; Smith, Dianne (Common Ground Publishing, 2014)
India has a rich and vibrant culture that is incredibly diverse in cultural and religious traditions, but at timesthis diversity can lead to conflict and prejudice. Attempts have been made—with varying degrees of success—to improve equality and equity. This is especially true in relation to the caste system. An Indian rural village—‘gaanv,’in Hindi— is a microcosm of this diversity and provides a fascinating case study that reflects wider issues facing Indian society today.In 2011 and 2012, a research team from Curtin University formed to partner with an NGO. The aim was to undertake a development assistance program on a heritage building just outside the Indian village of Lakhnu. As part of this research, a study of the village was undertaken. This study collected a variety of data, ranging from physical mapping to questionnaires completed by the villagers. The results of this study demonstrated a strong relationship between space in the village and its socio-cultural composition. Using the data collected, this paper will examine how caste, religion, and gender have affected the distribution of people and land uses within the village. Another theme of the paper is an exploration of how public places in the village are viewed by a range of its inhabitants.